P138 Baseline Hypoxemia Predicts Survival in Patients with Idiopathic Pulmonary Arterial Hypertension Without Patent Foramen Ovale. (19th November 2012) - Nair, A; Fuller, J; Crackett, R; Day, M; Lordan, J; Fisher, A; Corris, P
Abstract : Introduction and Objectives: The relevance of hypoxemia in patients with Idiopathic pulmonary arterial hypertension (IPAH) without Patent Foramen Ovale (PFO) on haemodynamics and survival is not well described. The aim of this study is to ascertain the severity and prevalence of hypoxemia in patients with IPAH without PFO, and its impact on survival. Methods: This is a single centre registry evaluation from 2001–2010 of patients attending the National Pulmonary Vascular Treatment Centre for Northern England. Outcomes were prospectively recorded on database following comprehensive assessment and confirmation with right heart catheterisation. PFO was excluded using bubble contrast ECHO. Data on arterial blood gas (ABG), lung function and radiology were obtained from case notes/hospital reporting systems. Patients initiated on targeted therapy were followed up at 3–4 month intervals. Results: ABG data was available for a cohort of 44 IPAH patients. 28(58%) were women. Mean age (SD) was 55.6(16.6) years, mean (SE) for Mean PAP 47(1.7) mm Hg, CI 2.18(0.09) L/min/m2, 6MWD 266(22) metres, PaO2 9.04(0.25) kPa, SPO2% 93(0.3), FEV1% 81.1(2.8), DLCO% 61.4(3.4). Mild Hypoxemia was seen in7(16%), Moderate Hypoxemia in 26(59%), Severe Hypoxemia in 11 (25%) patients respectively. There were significant differences in survival between groups (logrank P value 0.0012, Figure 1 ). Mean survival (95% CI) in mild, moderate and severe hypoxemia groups were 12.3 years (9.1 to 15.4), 6.84(4.8 to 8.8), and 2.8(1.6 to 3.9) years respectively. There were no correlations between PaO2 and haemodynamic measurements (RAP/CI/PVR)/FEV1/FC. A modest correlation r. 32 was observed between PaO2 and 6MWD, (P0.04). Conclusion: Baseline Hypoxemia is an independent predictor of survival whilst on targeted therapy and moderate hypoxemia is prevalent in the absence of PFO/lung disease in IPAH.